Exploring the nexus of disclosure of Sharia compliance and governance in Islamic banking: a comprehensive analysis of the sharia supervisory board / Arifah and Ataina Hudayati - -, Arifah; Hudayati, Ataina (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2023)
This research provides an in-depth examination of the crucial connection between Sharia Supervisory Boards (SSB) and Sharia Compliance Disclosure (SCD) in the context of Indonesian Islamic banks. Using secondary data from the years 2014 to 2019, sourced from a selection of Islamic Banks, this research employed panel multiple regression analysis conducted using E-Views software. The findings of this investigation yielded remarkable insights. Firstly, it was demonstrated that the expertise of SSB members played a pivotal role in significantly and positively influencing the extent of SCD. Conversely, the size and education of SSB members exerted a significant and negative influence on SCD. Intriguingly, the study revealed that SSB's meetings and SSB's cross-directorship did not have any impact on SCD. These findings hold profound implications for the strategic selection and composition of SSB, highlighting the paramount importance of expertise in driving robust SCD practices within Islamic Banks. In this way, this research advances our understanding of SSB dynamics and their impact on financial transparency, contributing valuable insights to the global discourse on Islamic finance.